Redescription and review of the Neotropical genus Carohamilia Dyar, 1940 (Lepidoptera: Cossidae: Zeuzerinae) - Naydenov, Artem E.; Yakovlev, Roman V.; Penco, Fernando C. (Zootaxa, 2021)
Based on the study of type specimens, we provide a redescription of the little known tropical genus of Cossidae (Lepidoptera), Carohamilia Dyar, 1940 (type species − Carohamilia ophelia (Schaus, 1921)). We establish the new combinations: Carohamilia masoni (Schaus, 1894), comb. n., Carohamilia terrafirma (Schaus, 1911), comb. n., Carohamilia poam (Dyar, 1918), comb. n., Schreiteriana lineaeplena (Dognin, 1911), comb. n., and a new synonym: Schreiteriana lineaeplena (Dognin, 1911) = Schreiteriana urcuchillay Yakovlev, Penco and Witt, 2017, syn. n.